FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA DI KECAMATAN DENPASAR SELATAN - Ketut Ayuningsasi, Kadek Ade Sugi Prananta, Anak Agung (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 11 (2019): Vol. 8, No.11, November 2019, pp (2501-2806), 2019)
The difficulty of the economy makes people choose one alternative business in the informal sector, with relatively small capital to support their needs, one of them being street vendors. The objectives to be achieved in this study are: 1) to analyze the effect of simultaneous outpouring of work hours, length of business, capital and location of trading on street vendor income in South Denpasar District, 2) to analyze the effect of partially spread of work hours, length of business , capital and location of trading to the income of street vendors in South Denpasar District. The data analysis technique used is multiple linear regression analysis. The results of the data analysis show that 1) outflow of working hours, length of business, capital and location of trading simultaneously influence the income of street vendors in South Denpasar District, 2) outflow of working hours, length of business, capital have a positive and significant effect on the income of foot traders five in South Denpasar District, 3) settled trading locations have higher incomes than non-settled trading locations with street vendors in South Denpasar District.